Simple Power Quality Compensation with Bidirectional Battery Charger for Electric Vehicles in Single-Phase Three-Wire Distribution Feeders - Fuka Ikeda; Kei Nishikawa; Yuki Okamoto; Hiroaki Yamada; Toshihiko Tanaka; Masayuki Okamoto (Energies, 2020)
This paper deals with power quality compensation in single-phase three-wire distribution feeders using a constant DC-capacitor voltage-control (CDCVC)-based strategy of the previously proposed bidirectional battery charger (BBC) for electric vehicles under the distorted source-voltage and load-current conditions. Instantaneous active power flowing into the three-leg pulse-width-modulated (PWM) rectifier in the BBC is discussed. The instantaneous power flowing into the three-leg PWM rectifier demonstrates that the CDCVC-based strategy obtains balanced and sinusoidal source currents at a unity power factor, where the source-side active power is balanced with the load-side active power. Simulation and experimental results demonstrate that balanced and sinusoidal source currents at a unity power factor are attained in single-phase three-wire distribution feeders with both battery-charging and -discharging operations for electric vehicles even though both source voltage and load currents are distorted.